Bandung's Superior Branding Strategy for the 213th Anniversary of the City of Bandung on Instagram - Chaerunnisa, Puteri Devina; Parsono, Slamet (Program Studi Ilmu Komunikasi FBIK Unissula, 2024)
The Bandung City Public Relations branding strategy is an important reference in disseminating information to make Bandung superior in the 213th Anniversary of the City of Bandung. Instagram has become an effective social media for Bandung City Public Relations in disseminating this information. The purpose of this research is to find out how Bandung's branding strategy excels at the 213th Anniversary of the City of Bandung on Instagram @humas_bandung. Researchers use methods through a qualitative approach by collecting data from interviews, observations and documentation. This research uses branding strategies, namely fact finding, planning, action and communication, and evaluation of activities. In the search for facts, Public Relations of the City of Bandung analyzed the data and facts of the 213th Anniversary of the City of Bandung and the application of the Bandung Superior tagline In making plans, Public Relations for the City of Bandung describes the data and facts in the agenda setting Bandung City Public Relations produces content and distributes it via Instagram; and Bandung City Public Relations evaluates each content to find out how far the Superior Bandung message has reached the public.